Correlation between Nutritional Status, Energy Intake, and VO2Max Level in Female Futsal Players - Wulandari, Cindy (Journal of Physical Education Health and Sport, 2021)
The purpose of this study was to discover the correlation between nutritional status, intake of energy, and VO2Max level in female futsal players. The method used is quantitative correlation with the research design of Cross Sectional Study. The subjects in this study used female futsal players from Antartika Senior High School Sidoarjo with an age range of 15-18 years with a total of 30 people. Data were collected using measurements of height and weight, food recall 2x24 hours, and Multistage Fitness Test (MFT). Data analysis using Rank Spearman. Based on the results of the study, it can be concluded that there is a correlation between nutritional status and VO2Max (r= -0.427 and p= 0.019) and there is a correlation between nutritional status and energy intake with values of r= 0.646 and p= 0.000. However, there is no correlation between energy intake and VO2Max (r=0.080 and p= 0.674). Â